Consensus planning in transport: The case of Vancouver's transportation plebiscite. (February 2019) - Legacy, Crystal; Stone, John
Abstract: In 2015, a plebiscite was held on a new source of funding to support the expansion of the transit network in the Lower Mainland of Vancouver. Thus, in a region that has achieved admirable results over several decades through a strategic planning system based on a consensus model, civic leaders were forced to step outside this model to argue the case for a 0.5% increase to a local goods and service tax. This pitted a 'no new tax' grouping against a Better Transit and Transportation Coalition which brought supporters from across the community including from business, the unions, the environmental sector and students in support of the 'yes' case and the package of works crafted by consensus among municipal leaders. In this paper, we draw on in-depth key informant interviews with transportation and land use planners, municipal politicians and individuals involved in the 'yes' and 'no' campaigns built around the 2015 transport plebiscite. We show how the plebiscite was framed and how a critical component of Vancouver's planning ethos – consensus decision-making – catalysed the formation of the coalition of 'yes' campaign supporters. Despite its defeat, this coalition remained persistent and unified in their support for the development of a new funding stream and for the continued expansion of transit infrastructure across the Lower Mainland. The paper draws lessons from the transit plebiscite and how its outcome highlight the unique role that consensus planning can play in achieving progressive outcomes to politically vexing questions in transport planning in Vancouver and elsewhere.